Guide to business planning - Friend, Graham; Zehle, Stefan (London : The economist in association with Profile Books, 2004)
This guide covers every aspect of preparing a business plan, including how to analyze the market, how to model the business and financial statements, the analysis of risk and the assessment of both the upside and potential downside, and the all-important executive summary--often the only part of a business plan that is read. Finally, it shows how to use a business plan to help put your ideas into practice and how to monitor and measure the performance of the business.--From publisher description.
At head of title: The Economist.
Includes bibliographical references and index.
Keywords: Business planning